PENDIDIKAN POLITIK OLEH KADER PDI PERJUANGAN PROVINSI RIAU TAHUN 2015-2016 - Heatubun, Benedicto Solleander; Tinov, M.Y. Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
After the reformation in Indonesia in 1998 the life of the Indonesian nation has undergone many changes, one of them in the political field, where for 32 years under the authoritarian government of an authoritarian new order. The change was marked by the amendment of the 1945 Constitution four times in the period 1999 to 2002. The existence of the amendment impact on political freedom, among others, with the birth of new political parties both ideologically religious and nationalist. The election participants in 1999 differed markedly from the election during the New Order period, during which the New Order period was only followed by two political parties (PDI and PPP) as well as one Golongan Karya (GOLKAR) and in the 1999 election followed by 48 old political parties as well new. As a democratic country, the presence of a political party is a necessity, in which its presence is expected to become a channel for the aspirations of society, the balance of political power and as a means of criticizing and controlling the ruling government. However, with many political parties, it is not uncommon for clashes of political interests between parties, so the tendency of political parties to focus more on the interests of their own party and forget its main function as channeling the aspirations of the people.Political education is a very important agenda. Because in carrying out the development of a nation requires a requirement for the political education of the people. The politically-educated citizen is a citizen, so he can consciously participate independently or indirectly in the development process. The presence of political parties can be seen in its role in passing political education to the people. With the political education of the community it is possible to have an ideal political culture, namely awareness to support the political system and also provide criticism and correctionKeywords : Political education, political parties, PDI Perjuangan